The effect of demonstrating the kinetic model using an instructional video in learning the human wheel movement (kart wheel) on the floor exercise mat in men's artistic gymnastics - Muhammad, L.Dr. Oras Qasim; Musleh, L.Dr. Omar Ahmed; Nasser, L.Dr. Malek Gamal Abdel (Sulaimani Journal for Humanities, 2026)
This research aimed to identify the effect of presenting a movement model using an instructional video on learning the human wheelie on the floor exercise mat, and to identify the difference between using the movement model with the aid of the instructional video and the traditional method used to learn the human wheelie on the floor exercise mat. The research was conducted on a sample of 20 second-year students from the College of Physical Education and Sports Sciences at Anbar University during the 2024-2025 academic year. The students were divided into two groups of 10 students each. The movement model using the instructional video was applied to the experimental group, while the control group followed the traditional method. The movement model using the instructional video was applied to the experimental group only during the practical part of the weekly training unit, for two training units per week, from October 6, 2024, until Wednesday, October 24, 2024. The researchers concluded that both the presentation of the movement model using an instructional video and the method employed had a significant impact on learning the movement under study. However, the presentation of the movement model using an instructional video had the greatest impact on learning this particular movement. The researchers attribute this to the fact that presenting the movement model using an instructional video gave the learner a broader, more comprehensive, and more precise understanding of the movement to be performed. In light of the above, the researchers recommend the necessity of using modern learning methods, especially those related to educational technology, in learning gymnastics movements on various equipment.